Measuring First Normal Stress Difference at Higher Shear Rates via Capillary Rheometer (Annual Transactions of the Nordic Rheology Society, 2025)
First normal stress difference is commonly measured in cone-plate geometries up to the shear rates of around 10 s-1 with rotational rheometers. At higher shear rates, the measurement is limited either by the torque or normal force threshold of the instrument or by some material-related limitations e. g., edge fracture. A new Normal Stress die designed to simultaneously measure steady-state shear viscosity and first normal stress difference at higher shear rates (>>10 s-1 ) via a capillary rheometer is first introduced. Measured data of the first normal stress difference are then correlated to the onset of flow instabilities, like shark skin of plastics and poor extrusion of rubber compounds, detected by the Garvey die. Here, dimensionless numbers are introduced to increase selectivity. First normal stress difference measurement also opens an easy and effective way to analyse the die drool effect.